How do extreme ENSO events affect Antarctic surface mass balance? - J. M. A. Macha; A. N. Mackintosh; F. S. McCormack; B. J. Henley; B. J. Henley; H. V. McGregor; H. V. McGregor; C. T. van Dalum; A. Purich (The Cryosphere)
Extreme El Niño–Southern Oscillation (ENSO) events have far-reaching impacts globally, yet their impacts on Antarctica are poorly understood. In particular, how extreme ENSO events influence Antarctica's mass balance remains uncertain, with few studies considering how extreme events could differ from moderate events. Here, we examine the impacts of past extreme El Niño and strong La Niña events over the period 1979–2018 on the surface mass balance (SMB) of Antarctica using a reanalysis-forced regional climate model. We find that Antarctic surface mass balance does not vary significantly during most of the simulated extreme events. Based on only three (five) events in the observational period, regional anomalies differ during the extreme El Niño (La Niña) events considered and cannot be generalised. Enderby Land is an exception: significant increases in surface mass balance – approximately 32 % of the regional annual average – occur during all extreme El Niño events considered. Furthermore, for the 2015/16 El Niño, surface mass balance changes across Antarctic catchments extend beyond the 5th and 95th probability distributions for September–November (SON) averages for the full 1979 to 2018 period (much further inland than during other extreme El Niño events), suggesting these changes are not consistent with background conditions. Our results suggest that future extreme ENSO events may continue to cause significant impacts on Antarctic surface mass balance. However, the magnitude and polarity of the potential impacts cannot be inferred from the limited information available on extremes contained in 4 decades of historical data. Further investigations using ice core data and large ensemble model simulations are needed to better understand the drivers of the spatial and temporal variability in this system.